The concentrations and sources of PAHs and PCBs in soil from an oil field and estuary in the Yellow River Delta, China - Jianrong, Cao; Yanjun, Liu; Sujie, Yu (Frontiers in Environmental Science, 2022)
The occurrence of organic pollutants [i.e. polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs)] had been assessed in the soil samples collected from two sub-regions (an oil field and the Yellow River Estuary) in the Yellow River Delta (YRD), China. The concentrations of PAHs and PCBs in the soil were in the range of 157.8–481.7 μg kg−1 (dry weight) and 5.6–56.6 μg kg−1 (dry weight), respectively. The average concentration of PAHs in the soil samples from the oil field were 274.0 μg kg−1, and that in the estuary soil samples were 244.4 μg kg−1. The average concentration of PCBs in the soil samples from the oil field and the estuary were 24.2 μg kg−1 and 10.8 μg kg−1, respectively. The contribution of low molecular weight PAHs (two-ring and three-ring PAHs) was larger in the soil samples from the oil field than that in the estuary soil samples. Both PAHs and PCBs contaminations in the estuary area were lower than that in the oil field area. By using diagnostic ratios analysis, the main source of PAHs was attributed to petroleum input caused by the fuel oil or light refined petroleum products in the Gudong Oilfield. The amount of low-chlorine congeners (three to four chlorine atoms) PCBs in soil samples from the oil field were higher than that in the estuary soil samples. The congeners analysis of PCBs and the correlation analysis between the concentrations of PAHs and PCBs were employed. The results indicated that the emission of PCBs in YRD were influenced by both Gudong oilfield and other industrial sources.